Study of nanostructured layers of single-crystal silicon by scanning tunnel spectroscopy - Kulyk, S.P.; Melnichenko, M.M.; Svezhentsova, K.V.; Shmyryova, O.M. (Functional Materials, 2008)
The nanostructured silicon surface has been studied using the scanning tunnel microscopy and spectroscopy in air. The local density of electron states was defined as normalized differential tunnel conductivity (dI/dU)(I/U). The surface morphology has been found to be characterized by the presence of a homogeneous nanostructure on the initial substrate microrelief. For the first time it has been shown that the spectrum of electron states changes considerably during the growth of a nanostructured silicon film.